2024
DOI: 10.1021/acs.inorgchem.4c00033
|View full text |Cite
|
Sign up to set email alerts
|

Hg3Se(SeO3)(SO4): A Mixed-Valent Selenium Compound with Mid-Infrared Transmittance Obtained by In Situ Reaction

Peng-Fei Li,
Chun-Li Hu,
Bing-Xuan Li
et al.

Abstract: Exploring new material systems is a highly significant task in the field of inorganic chemistry. A new mixed-valent selenium compound, Hg 3 Se(SeO 3 )(SO 4 ), was successfully synthesized through in situ reactions. This compound exhibits a novel three-dimensional structure composed of Hg 3 Se(SO 4 ) layers bridged by SeO 3 trigonal pyramids. It is the first structure containing (SeO 3 ) 2− , (SO 4 ) 2− , and Se 2− simultaneously. In addition, Hg 3 Se(SeO 3 )(SO 4 ) possesses a wide bandgap (3.5 eV), moderate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 58 publications
0
1
1
Order By: Relevance
“…The experiments revealed that the LIDT value for Pb 2 (SeO 3 )(SiF 6 ) is 50.8 MW cm −2 , approximately 19.5 times higher than that of AgGaS 2 (2.6 MW cm −2 ). This value is slightly higher than those previously reported for the compounds Hg 3 Se(SeO 3 )(SO 4 ) (23.35 MW cm −2 ) 57 and Pb 3 (TeO 3 )Br 4 (21.5 MW cm −2 ). 45 …”
Section: Resultscontrasting
confidence: 59%
“…The experiments revealed that the LIDT value for Pb 2 (SeO 3 )(SiF 6 ) is 50.8 MW cm −2 , approximately 19.5 times higher than that of AgGaS 2 (2.6 MW cm −2 ). This value is slightly higher than those previously reported for the compounds Hg 3 Se(SeO 3 )(SO 4 ) (23.35 MW cm −2 ) 57 and Pb 3 (TeO 3 )Br 4 (21.5 MW cm −2 ). 45 …”
Section: Resultscontrasting
confidence: 59%
“…The Hg + cations are presented as Hg 2 2+ in a dumbbell-like configuration with the Hg–O and Hg + –Hg + bond lengths in the ranges of 2.129(9)–2.643(9) and 2.5255(7)–3.3617(7) Å, respectively. These bond lengths are close to those reported in the known mercurous oxide compounds. ,− The Hg(1)–Hg(3) and Hg(2)–Hg(4) dumbbells are connected with two oxygen atoms in the linear [O(1)–Hg(1)–Hg(3)–O(5)] and [O(4)–Hg(2)–Hg(4)–O(2)] groups. The bond valences of Hg, Te, and S were calculated to be 0.531–0.826, 3.721–3.780, and 5.857–5.860, indicating that their oxidation state is +1, +4, and +6, respectively (Table S2).…”
Section: Resultsmentioning
confidence: 99%